Efektivitas Penggunaan Aplikasi Examview di SMA PGRI 2 Sampit - muhajir, ahmad; Supriatin, Atin; Supriyadi, Bambang; Fathurrahman, Fathurrahman; Fauzannur, Fauzannur (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The objective of this study is to assess the efficacy of utilising the ExamView application in the assessment and evaluation process at SMA PGRI 2 Sampit. The ExamView application has been developed with the specific intention of assisting teachers in the creation of examination questions, the acceleration of the correction process, and the provision of comprehensive analysis of the results. This research employed a descriptive quantitative methodology with a purposive sampling technique, encompassing a sample of 17 teachers and 236 students. The data were collected through the administration of questionnaires, the conduct of observations, and the facilitation of interviews. The findings indicated that the utilisation of the ExamView application has the potential to enhance the efficacy and calibre of the learning evaluation process. Approximately 14 of teachers reported that the application made it easier to create questions and to correct them more quickly. In addition, 177 of students felt that the exams were more structured and that they were more motivated. Nevertheless, challenges remain in terms of enhancing teachers' technological proficiency and addressing infrastructure limitations, such as unreliable internet connectivity. With these improvements, the ExamView application has the potential to make a more pronounced impact on the learning evaluation process at SMA PGRI 2 Sampit. This research underscores the necessity for supplementary training for teachers and enhanced technical resources to fully leverage technology in education